Rotation parameter estimation error of deflectometer basic unit - Phuong, Hoang Anh; Gorbachev, A.A.; Konyakhin, I.A.; Hoa, Tong Minh (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2019)
Subject of Research. The paper proposes a method for determining the rotation parameters of the basic unit of an opticalelectronic deflectometer, having an effect on the deflection measurement error of large-scale objects such as a floating dock. Method. We proposed an algorithm and mathematical model structure for the effect of the image coordinate estimation error of the collimating mark on the rotation parameter estimation error of the deflectometer basic unit with the use of the elements of vector algebra and matrix analysis. Main Results. We have proved that the rotation parameters of the basic unit can be determined as a result of solution of nonlinear equation systems based on the Levenberg–Marquardt optimization algorithm. Studies on a mathematical model have given the possibility to estimate the effect of the image coordinate estimation error of the collimating mark on the rotation parameter estimation error of the basic unit. Practical Relevance. The results of this work will enable us to develop an algorithm for compensation of the basic unit rotation parameters due to the effect of external factors and, as a result, to reduce the error in determining the spatial coordinates of the controlled object (deflection of the floating dock).